2013
DOI: 10.1371/journal.pgen.1003792
|View full text |Cite
|
Sign up to set email alerts
|

Nebula/DSCR1 Upregulation Delays Neurodegeneration and Protects against APP-Induced Axonal Transport Defects by Restoring Calcineurin and GSK-3β Signaling

Abstract: Post-mortem brains from Down syndrome (DS) and Alzheimer's disease (AD) patients show an upregulation of the Down syndrome critical region 1 protein (DSCR1), but its contribution to AD is not known. To gain insights into the role of DSCR1 in AD, we explored the functional interaction between DSCR1 and the amyloid precursor protein (APP), which is known to cause AD when duplicated or upregulated in DS. We find that the Drosophila homolog of DSCR1, Nebula, delays neurodegeneration and ameliorates axonal transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 97 publications
1
45
1
Order By: Relevance
“…AD-associated presenilin 1 mutations and hyperphosphorylated tau have also been shown to induce axonal transport defects through activation of GSK3b [25,96,98]. Correcting fast axonal transport defects by reducing GSK3b activity was found to be beneficial in a Drosophila model of AD [99,100]. Deregulation of Cdk5 is also linked to defects in the slow axonal transport of neurofilaments in AD [77].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…AD-associated presenilin 1 mutations and hyperphosphorylated tau have also been shown to induce axonal transport defects through activation of GSK3b [25,96,98]. Correcting fast axonal transport defects by reducing GSK3b activity was found to be beneficial in a Drosophila model of AD [99,100]. Deregulation of Cdk5 is also linked to defects in the slow axonal transport of neurofilaments in AD [77].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Therapeutic interventions can be aimed at the specific phosphotransferase activities relevant to AT deficits. Hence, some studies on AD are beginning to focus on investigating proteasome activities; for example, a few recent studies have examined the way proteasomeassociated protein Nedd8 ultimate buster (NUB1)-induced GSK3β degradation [98,99].…”
Section: Development Of Effective Therapies Targeting Atmentioning
confidence: 99%
“…Increases in Et STP may also be related to drug efflux from the cell, which decreases effective intracellular drug concentrations. Indeed, a study by Shaw and Chang () showed that PP2B is involved in axonal transport. The results of these studies and the present study demonstrated that upregulation of Et STP may be related to drug resistance.…”
Section: Discussionmentioning
confidence: 99%